Insight into nuclear body formation of phytochromes through stochastic modelling and experiment. (18th May 2018) - Grima, Ramon; Sonntag, Sebastian; Venezia, Filippo; Kircher, Stefan; Smith, Robert W; Fleck, Christian
Abstract: Spatial relocalization of proteins is crucial for the correct functioning of living cells. An interesting example of spatial ordering is the light-induced clustering of plant photoreceptor proteins. Upon irradiation by white or red light, the red light-active phytochrome, phytochrome B, enters the nucleus and accumulates in large nuclear bodies (NBs). The underlying physical process of nuclear body formation remains unclear, but phytochrome B is thought to coagulate via a simple protein–protein binding process. We measure, for the first time, the distribution of the number of phytochrome B-containing NBs as well as their volume distribution. We show that the experimental data cannot be explained by a stochastic model of nuclear body formation via simple protein–protein binding processes using physically meaningful parameter values. Rather modelling suggests that the data is consistent with a two step process: a fast nucleation step leading to macroparticles followed by a subsequent slow step in which the macroparticles bind to form the nuclear body. An alternative explanation for the observed nuclear body distribution is that the phytochromes bind to a so far unknown molecular structure. We believe it is likely this result holds more generally for other nuclear body-forming plant photoreceptors and proteins.